Penguatan Jiwa Kewirausahaan Mahasiswa melalui Strategi Pemasaran Digital - Yudhi Novriansyah; Supriyati Supriyati; Herawati Herawati; Muhammad Asman; Ida Zuliyana (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Lectures of the Management Study Program at Muara Bungo University (UMB) have implemented a Community Service Program (PKM) to boost students' entrepreneurial spirit. This was carried out through a seminar and discussion with the theme